The Effect of Risk Prevention Ability on Entrepreneurial Performance of Chinese College Students: Moderating Effect of Team Management Ability - Zhu, Yuting; Qu, Shaowei; Jin, Hebo; Li, Zhaohui (Frontiers in Psychology, 2022)
Improving the performance and success rate of college students’ new ventures has attracted increasing attention globally. In this study, a questionnaire survey was conducted among 115 college students who were directly involved in entrepreneurial activities in 23 provinces in China. The study explores the effects of team management and risk prevention abilities on college students’ entrepreneurial performance. The results show that risk prevention ability significantly increases university students’ entrepreneurial performance (including profit and loss status, capital flow, and staff flow). Team management ability enhances these entrepreneurial indicators to varying degrees, with a ‘threshold’ effect of its impact on entrepreneurial performance. With a continued increase in team management ability, the effect of risk prevention ability on entrepreneurial performance becomes increasingly more significant. Specifically, when team management ability reaches a medium level and above, risk prevention ability significantly improves capital flow and staff stability; and when team management ability reaches a high level, risk prevention ability significantly improves enterprise profitability indicators.